Co-presence of hydrophilic and hydrophobic sites in Ni/biochar catalyst for enhancing the hydrogenation activity. (1st June 2021) - Wang, Yiran; Shao, Yuewen; Zhang, Lijun; Zhang, Shu; Wang, Yi; Xiang, Jun; Hu, Song; Hu, Guangzhi; Hu, Xun
Graphical abstract: Highlights: Polarity of Ni/biochar catalyst affects hydrogenation of biomass derivatives. HNO3 treatment increase the hydrophobicity of the biochar carrier. Co-presence of hydrophobic/hydrophilic sites facilitate adsorption of vanillin. 1-chloro-2-nitrobenzene hydrogenation is not sensitive to hydrophilic sites. Hydrophilic sites enhance the activity for hydrogenation of vanillin and eugenol. Abstract: Hydrophilicity/hydrophobicity is one of the most important parameters in heterogenous catalysts, as it significantly impacts the adsorption and activation of the reaction substrate. In this study, we have demonstrated that the treatment of the biochar derived from the pyrolysis of rice husks with HNO3 oxidation and subsequent thermal treatment could remarkably increase the overall hydrophobicity of the Ni catalyst termed as Ni/biochar (treated). However, owing to the un-uniform surface of the biochar, some hydrophilic sites also exist. The co-presence of the hydrophobic and hydrophilic sites in the Ni/biochar (treated) facilitates the adsorption/activation of the CO functionality in vanillin and the aliphatic CC in eugenol. This renders the Ni/biochar (treated) catalyst with the much higher activity for hydrogenation of the unsaturated bonds than the Ni/biochar (un-treated) catalyst with mainly the hydrophilic sites. The reaction substrate like 1-chloro-2-nitrobenzene that could not form strong hydrogen bond with the biochar was less sensitive to the hydrophilicity/hydrophobicity of the catalyst. The results herein provide some reference information for optimizing catalytic performance via tailoring surface properties.